Modeling the Dependence of Losses of a Financial Portfolio Using Nested Archimedean Copulas - Wendkouni Yaméogo; Diakarya Barro (International Journal of Mathematics and Mathematical Sciences)
In financial analysis, stochastic models are more and more used to estimate potential outcomes in a risky framework. This paper proposes an approach of modeling the dependence of losses on securities, and the potential loss of the portfolio is divided into sectors each including two subsectors. The Weibull model is used to describe the stochastic behavior of the default time while a nested class of Archimedean copulas at three levels is used to model the maximum of the value at risk of the portfolio.